ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH PENERAPAN E-COMMERCE (STUDI PADA PERUSAHAAN SUB SECTOR RETAIL TRADE DALAM INDEX SAHAM SYARIAH INDONESIA (ISSI) DI BURSA EFEK INDONESIA) - Akbar Akbar; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2021)
This research was conducted to determine whether there are differences in the financial performance of companies in the retail trade sub-sector which are included in the Indonesian Sharia Stock Index (ISSI) in the Indonesia Stock Exchange between before and after the implementation of e-commerce. The data analysis technique used in this study was the Paired Sample T-test for normally distributed data and the Wilcoxon Sign Rank Test for data that were not normally distributed. The variables analyzed consisted of profitability ratios as proxied by Return On Assets (ROA); liquidity ratio which is proxied by Current Ratio (CR); solvability ratio which is proxied by Debt to Assets Ratio (DAR); and the activity ratio which is proxied by Total Assets Turnover (TATO). Based on the results obtained in this study for the variables ROA, DAR, and TATO, it shows that there is a significant difference between before and after the implementation of e-commerce. Meanwhile, the CR variable shows that there is no significant difference between before and after the implementation of e-commerce. Keywords: Financial Performance, Information & Technology Development, E-Commerce